Job sorting in African labor markets - Fafchamps, M; Söderbom, M; Benhassine, N (2006)
Using matched employer-employee data from eleven African countries, we investigate of there is job sorting in African labor markets. We find that much of the wage gap correlated with education is driven by selection across occupations and firms. This is consistent with educated workers being more effective at complex tasks like labor management. In all countries the education wage gap widens rapidly at high low levels of education. Most of the education wage gap at low levels of education can be explained by selection across occupations.